Work related physical activity and risk of a hospital discharge diagnosis of atrial fibrillation or flutter: the Danish Diet, Cancer, and Health Study. Issue 1 (21st December 2004) - Frost, L; Frost, P; Vestergaard, P
Abstract : Background and Aims: Excessive sporting activities have been associated with risk of atrial fibrillation. To study if work related physical activity also confers risk of atrial fibrillation or flutter, the association between work related physical strain and the risk of a hospital discharge diagnosis (inpatient as well as outpatient) of atrial fibrillation or flutter was examined. Methods: A population based prospective cohort study was conducted from December 1993 to December 2001 among 19 593 men and 18 807 women with a mean age at baseline of 56 years (range 50–65 years) in the Danish Diet, Cancer, and Health Study. The physical strain during working hours was categorised as sedentary, light, or heavy, and analysed using proportional hazard models. Subjects were followed up in the Danish National Registry of Patients and in the Danish Civil Registration System. Results: During follow up (mean 5.7 years) a hospital discharge diagnosis of atrial fibrillation or flutter occurred in 305 men and 113 women. When using the risk of atrial fibrillation or flutter associated with sedentary work at a sitting position as a reference, no excess risk (unadjusted as well as adjusted) was found of atrial fibrillation or flutter associated with sedentary work in a standing position, light workload, or heavy workload in men or women. Conclusion: No evidence was found of an association between physical activities during working hours and risk of a hospital discharge diagnosis of atrial fibrillation or flutter for men and women in the age group of 50–65 years.